2023
DOI: 10.3390/molecules28145508
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxidation and Nitrogenation on the Physicochemical Properties and Sorption Capacity of Activated Biocarbons Prepared from the Elderberry Inflorescence

Wiktoria Dąbrowska,
Mateusz Gargol,
Małgorzata Gil-Kowalczyk
et al.

Abstract: The main objective of the study was to prepare a series of new activated biocarbons by means of physical and chemical activation of elderberry inflorescence. The influence of carbon matrix nitrogenation/oxidation on the physicochemical properties and sorption abilities of the carbonaceous materials was investigated. The impact of initial dye concentration, pH and temperature of the system on methylene blue and rhodamine B removal efficiency was checked. It was shown that activation of elderberry inflorescences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The results of a study performed by Zhang et al [42] showed that the hydrogen content in pine sawdust was 5.2%, while pine needles examined by Font et al [43] contained 6.5% of hydrogen. The hydrogen content in elderberry inflorescences is much higher than in the tested postproduction herbaceous waste from elderberry; in the study conducted by D ąbrowska et al [41], the hydrogen content was 7.2%.…”
Section: Elemental Composition Of Raw Materialsmentioning
confidence: 83%
See 2 more Smart Citations
“…The results of a study performed by Zhang et al [42] showed that the hydrogen content in pine sawdust was 5.2%, while pine needles examined by Font et al [43] contained 6.5% of hydrogen. The hydrogen content in elderberry inflorescences is much higher than in the tested postproduction herbaceous waste from elderberry; in the study conducted by D ąbrowska et al [41], the hydrogen content was 7.2%.…”
Section: Elemental Composition Of Raw Materialsmentioning
confidence: 83%
“…The analyzed elderberry waste contained slightly more sulfur (0.03%) than sawdust. In studies conducted by D ąbrowska and colleagues, the sulfur content in elderberry inflorescences was 0.6% [41].…”
Section: Elemental Composition Of Raw Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…Simultaneously, the chemical structure of the AC surface created a new active site. Calcination under the N 2 atmosphere produced a nitrogen site and decreased oxygen molecules (Dąbrowska et al 2023).…”
Section: Effect Of Oxygen-blowing and Temperature On Surface Propertiesmentioning
confidence: 99%
“…In addition, carbon-based composites are employed for lithium-ion batteries [14][15][16]. This Special Issue also includes investigations related to pollutant removal with sorption capability [17][18][19][20][21][22][23]. The preparation and adsorption performance of activated carbon are emphatically discussed [19,20].…”
mentioning
confidence: 99%